2017
DOI: 10.17269/cjph.108.6048
|View full text |Cite
|
Sign up to set email alerts
|

Ethical challenges in FASD prevention: Scientific uncertainty, stigma, and respect for women’s autonomy

Abstract: Fetal alcohol spectrum disorder (FASD) is a leading form of neurodevelopmental delay in Canada, affecting an estimated 3000 babies per year. FASD involves a range of disabilities that entail significant costs to affected individuals, families, and society. Exposure to alcohol in utero is a necessary factor for FASD development, and this has led to FASD being described as "completely preventable". However, there are significant ethical challenges associated with FASD prevention. These challenges revolve around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…A clear tension exists between 1) public health and medical guidelines requiring clear and actionable messages; 2) ensuring that marginalized women feel supported throughout their pregnancies; and 3) the importance of communicating the truth about research findingseven if that truth involves complexities. If media were to communicate only the clear but rigid message of abstinence in all cases, then the previously outlined issues of stigmatisation could arise, along with questions about paternalistic approaches to women's healthcare [53]; however, if contradictions are reported without care, some worry that this could provide women with a "license to drink" [50]. In our sample, contradiction more often appeared without comment between, rather than within, articles.…”
Section: When Can Clear and Certain Messaging Backfireand What Messagmentioning
confidence: 77%
See 1 more Smart Citation
“…A clear tension exists between 1) public health and medical guidelines requiring clear and actionable messages; 2) ensuring that marginalized women feel supported throughout their pregnancies; and 3) the importance of communicating the truth about research findingseven if that truth involves complexities. If media were to communicate only the clear but rigid message of abstinence in all cases, then the previously outlined issues of stigmatisation could arise, along with questions about paternalistic approaches to women's healthcare [53]; however, if contradictions are reported without care, some worry that this could provide women with a "license to drink" [50]. In our sample, contradiction more often appeared without comment between, rather than within, articles.…”
Section: When Can Clear and Certain Messaging Backfireand What Messagmentioning
confidence: 77%
“…Although clear messaging and discourse that fosters negative public attitudes toward drinking while pregnant can be useful from a public health perspective (i.e., discouraging unhealthy behaviour at the population level), it could also unhelpfully stigmatise individual women who do drink [12,50]. The clarity and certainty of abstinence messaging could, in some cases, have an effect opposite to the one intended, rigidifying public opinion against women most in need of support, and driving those women 'underground' [31].…”
Section: When Can Clear and Certain Messaging Backfireand What Messagmentioning
confidence: 99%
“…In the current sample, the most influential perceived barriers to screening were patient denial/resistance to treatment, time limitations, and patient sensitivity to screening. It is possible that perceived patient denial, resistance, and sensitivity reflect providers’ concern about stigmatizing patients (Corrigan et al., ; Zizzo and Racine, ). Yet previous surveys showed that most pregnant women believe screening for alcohol use is important and do not mind being asked questions about their own use (Jones et al., ; Seib et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its significant and independent association between prenatal smoking and adverse birth outcomes, 22 cigarette smoking has been the most prevalent among pregnant women in our study, and has not been considered as stigmatizing to admit usage as admitting to illicit drug and alcohol use among pregnant women. 23,24 While our study findings are suggestive for providers to pay attention to nonresponders as potential evidence of under-reported substance use during pregnancy, our findings also indicate that selfreported cigarette smoking can be viewed potentially as an indicator of other substance and alcohol co-use leading to significantly adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 63%